FEATURES OF THE INTERRELATIONSHIP BETWEEN CHARACTERISTICS OF THE PERSONALITY TRAITS AND CRITERION INDICATORS OF ACADEMIC-SIGNIFICANT PROFESSIONAL-ORIENTED SUCCESS OF MODERN STUDENTS - Serheta, Ihor (European Science, 2025)
The aim of the scientific research was to established the features of the interrelationship between characteristics of the personality traits and criterion indicators of academic-significant professional-oriented success of modern students. In the course